A hydration temperature rise inhibitor with strong peak clipping and weak retarding, and its preparation method and application

The starch is treated by dry heat, and a hydration temperature rise inhibitor with moderate viscosity average molecular weight is prepared, which solves the problem of insufficient temperature rise and retarding effects of concrete in the prior art, and realizes effective temperature control and cracks of thin-walled concrete Prevention and control.

CN118978607BActive Publication Date: 2024-12-20中国水利水电第七工程局有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411456052.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2024-12-20
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The prior art has shortcomings in suppressing the temperature rise and retarding effect of concrete. The process is complex and has a great impact on the settling time, making it difficult to meet the temperature crack prevention and control needs of thin-walled structural concrete.

Method used

Starch is used as the main raw material, starch is treated by dry heat method, hydrolysis and repolymerization reaction are controlled, pH value is adjusted to 13~13.5, and a hydration temperature rise inhibitor with a viscosity average molecular weight of 25,000~30,000 is prepared, with cement dosage 0.5%~1.0% to inhibit the temperature rise and retarding effect of concrete.

Benefits of technology

Effectively reduce concrete temperature peaks, reduce early heating rate, extend initial settling time, reduce the risk of temperature cracks, and is simple in process, suitable for temperature control and crack prevention of large volume concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118978607B_ABST
    Figure CN118978607B_ABST
Patent Text Reader

Abstract

The invention discloses a hydration temperature rise inhibitor with strong peak clipping and weak retarding, and a preparation method and application thereof, which relates to the field of building material concrete admixtures. The preparation comprises the following steps: S1, starch, accelerator and water are mixed in a mass ratio of 100: 0.04-0.25: 40-70 to prepare starch slurry; S2, the starch slurry is dried at 40-60°C to obtain pre-dried starch with a moisture content of 10%-15% and a liquid phase pH of 13.0-13.5; S3, the pre-dried starch is dry-heat cracked at 155-185°C for 2-4h, and the pre-dried starch is ground and sieved after natural cooling to obtain the hydration temperature rise inhibitor. The hydration temperature rise inhibitor provided by the invention can rapidly swell in the typical temperature range (generally 30-50°C) where large-volume concrete begins to rapidly heat up, and adsorb and form a film on the surface of the main minerals and hydration products of cement, which can not only effectively reduce the hydration temperature rise rate of concrete and reduce the temperature peak, but also reduce the retarding effect caused by low-temperature swelling and adsorption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building material concrete admixtures, and in particular to a hydration temperature rise inhibitor with strong peak clipping and weak retarding, and a preparation method and application thereof. Background Art

[0002] The problem of temperature cracks in concrete has always been the focus of engineering construction. Unlike conventional large-volume concrete with large dimensions in three dimensions and slow heat dissipation rate, the length, width and thickness of thin-walled structural concrete such as tunnel linings, station and building side walls, rockfill dam panels, and foundation covers vary greatly, and the exposed surface of the structure is large. The temperature of the concrete can reach the peak temperature within 1 to 2 days after pouring, and then quickly drop to the stable temperature of the environment in the subsequent 3 to 7 days, with the maximum temperature drop usually exceeding 20°C. In the rapid cooling stage, the thin-walled structural concrete is subject to the combined influence of the tensile and compressive stress difference caused by the temperature difference between the inner and outer surfaces, as well as the tensile stress caused by the overall shrinkage under the constraints of the bedrock or other structural boundaries. The risk of temperature cracks is greater than that of conventional large-volume concrete.

[0003] By suppressing the temperature rise of concrete, reducing the temperature peak, and reducing the heating rate in the temperature rise stage, the tensile stress inside the concrete can be reduced, thereby reducing the risk of temperature cracks. Patents CN201410768428.0, CN201410010473.X, CN201510060172.2, CN201510061681.7, CN201510061641.2, CN201510062213.1, CN201510726919.3, CN201610323926.3, CN201610834784.7, CN201910170750.6, CN201910170750.7 2110067512.X discloses a series of starch-based cement hydration heat control materials and preparation methods, with two main technical routes: one is to use starch as raw material, adopt acid hydrolysis or enzymatic hydrolysis, and assist with cross-linking agent, ethanol, acid anhydride and other additives, and obtain them through hydrolysis reaction in low temperature (≤60℃) water bath, ultrasound or microwave radiation conditions; the other is to use polyether, small molecule sugar or dextrin as raw material, and obtain them through polymerization cross-linking reaction by adding cross-linking agent, redox initiator, etc. in low temperature (≤90℃) water bath or microwave radiation conditions. In the above methods, there are many types and quantities of additives used in key reaction steps, and a considerable part of them need to use high-energy equipment such as ultrasound and microwave, so the preparation process is complicated and the procedures are cumbersome. In addition, affected by the synthesis process, some cement hydration heat regulating materials have a greater impact on the setting time. For example, in a preparation method of a cement hydration heat regulating material with internal curing function disclosed in CN201811145217.6, the cement hydration heat regulating material is prepared by cross-linking reaction of starch, dextrin and acrylic acid. While reducing the peak hydration rate, it prolongs the setting time of concrete by 7 to 11 hours. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and to provide a strong peak-cutting and weak-retarding hydration temperature rise inhibitor with a simple process flow, which can effectively reduce the concrete temperature peak, reduce the early heating rate and has a low retarding effect, as well as a preparation method and application thereof.

[0005] The objective of the present invention is achieved through the following technical solutions:

[0006] A method for preparing a hydration temperature rise inhibitor with strong peak clipping and weak retarding, comprising the following steps:

[0007] S1. Mix starch, accelerator and water in a mass ratio of 100:0.04-0.25:40-70 to prepare starch slurry;

[0008] S2, drying the starch slurry at 40-60° C. to obtain pre-dried starch with a moisture content of 10%-15% and a liquid phase pH of 13.0-13.5;

[0009] S3. Dry-crack the pre-dried starch at 155-185°C for 2-4 hours, grind and sieve after natural cooling to obtain a hydration temperature rise inhibitor.

[0010] Wherein, the starch in S1 is one or more of wheat starch, potato starch, rice starch, tapioca starch, sweet potato starch or corn starch.

[0011] The promoter in S1 is one or more of lithium hydroxide, sodium hydroxide, potassium hydroxide, sodium carbonate or potassium carbonate.

[0012] The product in S3 is placed in air for natural cooling, ground and passed through a 50-mesh sieve.

[0013] The second aspect of the present invention provides a hydration temperature rise inhibitor with strong peak clipping and weak retarding, which is prepared by the above method. The viscosity average molecular weight of the hydration temperature rise inhibitor is 25000-30000, the complete swelling maturity is 150-250℃·min, and the 200 mesh sieve residue fineness is 10%-30%.

[0014] The third aspect of the present invention provides the use of the above-mentioned strong peak clipping, weak retarding hydration temperature rise inhibitor in concrete, wherein the dosage thereof is 0.5% to 1.0% of the mass of cement.

[0015] The beneficial effects of the present invention are:

[0016] The present invention uses starch from a wide range of sources as the main raw material and uses a dry heat method to treat the starch. During the dry heat process, the chemical reaction process of the starch mainly includes hydrolysis, glycosidic bond transfer and repolymerization, accompanied by a small amount of Maillard reaction. In order to balance the degree of hydrolysis reaction and repolymerization reaction, control the molecular weight of the main product and inhibit the generation of small molecular sugars, the entire dry heat process is prepared under high moisture content, high temperature and short time conditions. In order to further shorten the dry heat time, the pH value of the pre-dried starch is adjusted to 13-13.5 using an alkali metal hydroxide or carbonate, so that it has low-temperature gelatinization characteristics.

[0017] The hydration temperature rise inhibitor provided by the present invention can be dissolved and adsorbed in the typical temperature range (generally 30-50°C) where the mass concrete begins to heat up rapidly, thereby inhibiting the retarding effect caused by low-temperature dissolution and adsorption. At the same time, since the hydration temperature rise inhibitor directly acts on the dissolution process of the main mineral C3S in cement and the nucleation and growth process of the main hydration product C-(A)-SH, rather than acting on other minerals such as C2S, C3A, C4AF or other hydration products such as calcium hydroxide and AFt in cement, its typical dosage is calculated as a percentage of the cement dosage and can be controlled at a relatively low level of 0.5-1.0%. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The temperature test results of the mortar after adding the hydration temperature rise inhibitor of Examples 1 to 10;

[0019] Figure 2 The graph is a graph of the heating rate of the mortar after adding the hydration temperature rise inhibitor of Examples 1 to 10;

[0020] Figure 3 The temperature test result diagram of the mortar after adding the samples prepared in Comparative Examples 1 to 3;

[0021] Figure 4 This is a graph of the heating rate of the mortar after adding samples prepared in Comparative Examples 1 to 3. DETAILED DESCRIPTION

[0022] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0023] The raw materials used in the embodiments and comparative examples are as follows:

[0024] Corn starch: produced in Suzhou, Jiangsu, industrial grade, content ≥98%.

[0025] Potato starch: produced in Jinan, Shandong, food grade, content ≥99%.

[0026] Cassava starch: produced in Thailand, food grade, content ≥99%.

[0027] Wheat starch: produced in Chongqing, industrial grade, content ≥99%.

[0028] Sodium hydroxide: commercially available, purity ≥99%.

[0029] Potassium hydroxide: commercially available, purity ≥99%.

[0030] Starch-based cement hydration heat control material: commercially available, model HHC-S.

[0031] Example 1

[0032] Corn starch, sodium hydroxide and water are mixed in a mass ratio of 100:0.04:40 to prepare a starch slurry with a moisture content of 40%; the starch slurry is dried at 40-60°C to obtain a pre-dried starch with a moisture content of 10% and a liquid phase pH of 13; the pre-dried starch is placed at 185°C for dry heat cracking for 2 hours, placed in the air for natural cooling, ground, and passed through a 50-mesh sieve to obtain a hydration temperature rise inhibitor.

[0033] Example 2

[0034] Corn starch, potassium hydroxide, sodium hydroxide and water are mixed in a mass ratio of 100:0.1:0.1:50 to prepare a starch slurry with a moisture content of 50%; the starch slurry is dried at 40-60°C to obtain a pre-dried starch with a moisture content of 12% and a liquid phase pH of 13.5; the pre-dried starch is placed at 175°C for dry thermal cracking for 2.5 hours, placed in the air for natural cooling, ground, and passed through a 50-mesh sieve to obtain a hydration temperature rise inhibitor.

[0035] Example 3

[0036] Corn starch, sodium carbonate and water are mixed in a mass ratio of 100:0.06:60 to prepare a starch slurry with a moisture content of 60%; the starch slurry is dried at 40-60°C to obtain a pre-dried starch with a moisture content of 14% and a liquid phase pH of 13; the pre-dried starch is placed at 165°C for dry heat cracking for 3 hours, placed in the air for natural cooling, ground, and passed through a 50-mesh sieve to obtain a hydration temperature rise inhibitor.

[0037] Example 4

[0038] Corn starch, potassium carbonate and water are mixed in a mass ratio of 100:0.25:70 to prepare a starch slurry with a moisture content of 70%; the starch slurry is dried at 40-60°C to obtain a pre-dried starch with a moisture content of 15% and a liquid phase pH of 13.5; the pre-dried starch is placed at 155°C for dry thermal cracking for 4 hours, placed in the air for natural cooling, ground, and passed through a 50-mesh sieve to obtain a hydration temperature rise inhibitor.

[0039] Example 5

[0040] Potato starch, sodium hydroxide, potassium carbonate and water are mixed in a mass ratio of 100:0.02:0.02:40 to prepare a starch slurry with a moisture content of 40%; the starch slurry is dried at 40-60°C to obtain pre-dried starch with a moisture content of 10% and a liquid phase pH of 13; the pre-dried starch is placed at 155°C for dry thermal cracking for 4 hours, placed in the air for natural cooling, ground, and passed through a 50-mesh sieve to obtain a hydration temperature rise inhibitor.

[0041] Example 6

[0042] Potato starch, cassava starch, potassium hydroxide and water are mixed in a mass ratio of 70:30:0.25:70 to prepare a starch slurry with a moisture content of 70%; the starch slurry is dried at 40-60°C to obtain a pre-dried starch with a moisture content of 15% and a liquid phase pH of 13.5; the pre-dried starch is placed at 185°C for dry thermal cracking for 2 hours, placed in the air for natural cooling, ground, and passed through a 50-mesh sieve to obtain a hydration temperature rise inhibitor.

[0043] Example 7

[0044] Cassava starch, sodium hydroxide and water are mixed in a mass ratio of 100:0.05:50 to prepare a starch slurry with a moisture content of 50%; the starch slurry is dried at 40-60°C to obtain a pre-dried starch with a moisture content of 13% and a liquid phase pH of 13; the pre-dried starch is placed at 175°C for dry thermal cracking for 2.5 hours, placed in the air for natural cooling, ground, and passed through a 50-mesh sieve to obtain a hydration temperature rise inhibitor.

[0045] Example 8

[0046] Cassava starch, potassium hydroxide and water are mixed in a mass ratio of 100:0.18:60 to prepare a starch slurry with a moisture content of 60%; the starch slurry is dried at 40-60°C to obtain a pre-dried starch with a moisture content of 11% and a liquid phase pH of 13.5; the pre-dried starch is placed at 165°C for dry thermal cracking for 3 hours, placed in the air for natural cooling, ground, and passed through a 50-mesh sieve to obtain a hydration temperature rise inhibitor.

[0047] Example 9

[0048] Wheat starch, sodium hydroxide and water are mixed in a mass ratio of 100:0.04:40 to prepare a starch slurry with a moisture content of 40%; the starch slurry is dried at 40-60°C to obtain a pre-dried starch with a moisture content of 10% and a liquid phase pH of 13; the pre-dried starch is placed at 175°C for dry thermal cracking for 2 hours, placed in the air for natural cooling, ground, and passed through a 50-mesh sieve to obtain a hydration temperature rise inhibitor.

[0049] Example 10

[0050] Wheat starch, potassium hydroxide and water are mixed in a mass ratio of 100:0.25:70 to prepare a starch slurry with a moisture content of 70%; the starch slurry is dried at 40-60°C to obtain a pre-dried starch with a moisture content of 15% and a liquid phase pH of 13.5; the pre-dried starch is placed at 155°C for dry heat cracking for 3 hours, placed in the air for natural cooling, ground, and passed through a 50-mesh sieve to obtain a hydration temperature rise inhibitor.

[0051] Comparative Example 1

[0052] The preparation method involved in this comparative example comprises the following steps: dry-heat cracking the dried corn starch at 195° C. for 3 h, naturally cooling in air, grinding, and passing through a 50-mesh sieve to obtain a sample.

[0053] Comparative Example 2

[0054] The preparation method involved in this comparative example comprises the following steps: mixing corn starch and water in a mass ratio of 100:70 to prepare a starch slurry with a moisture content of 70%; drying the starch slurry at 40-60°C to obtain pre-dried starch with a moisture content of 20%; subjecting the pre-dried starch to dry heat cracking at 185°C for 2h, cooling it naturally in the air, grinding it, and passing it through a 50-mesh sieve to obtain a sample.

[0055] Comparative Example 3

[0056] The preparation method involved in this comparative example comprises the following steps: corn starch, sodium hydroxide and water are mixed in a mass ratio of 100:0.06:70 to prepare a starch slurry with a moisture content of 70%; the starch slurry is dried at 40-60°C to obtain a pre-dried starch with a moisture content of 15% and a liquid phase pH of 13; the pre-dried starch is subjected to dry heat cracking at 145°C for 4 hours, placed in the air for natural cooling, ground, and passed through a 50-mesh sieve to obtain a sample.

[0057] Comparative Example 4

[0058] The commercially available starch-based cement hydration heat control material is model HHC-S.

[0059] test:

[0060] The characteristic parameters of the samples obtained in Examples 1 to 10 and Comparative Examples 1 to 3 are shown in Table 1. Among them, the test method of the viscosity-average molecular weight is: weigh 0.6g of the sample and place it in a beaker, disperse it with 1mL of 95% ethanol, then add 60mL of 0.5mol / L potassium hydroxide solution, heat and stir in a boiling water bath for 10min, cool to room temperature, and then quantitatively transfer to a 100mL volumetric flask, and dilute to the scale with 0.5mol / L potassium hydroxide solution. In the Ubbelohde viscometer, add 15mL of the above-prepared solution with a pipette and inject it into the dry Ubbelohde viscometer, repeat the measurement of the solution, and the flow time in the Ubbelohde viscometer is 3 times (the error is less than 0.02s), and the average value is taken as the outflow time t1 of the sample solution, and the solution concentration is C1 at this time. Then add 5mL of 0.5mol / L potassium hydroxide solution, and test the flow time t2 according to the above method, and the solution concentration is C2 at this time. In the same way, add 5mL, 5mL, and 5mL of 0.5mol / L potassium hydroxide solution again, and measure the flow time t3, t4, and t5. At this time, the solution concentration is C3, C4, and C5. Finally, use 0.5mol / L potassium hydroxide solution to measure the pure solvent flow time t0 according to the above steps. The viscosity average molecular weight is calculated using the following formula:

[0061]

[0062] Where η r is the relative viscosity; η sp is the specific viscosity; [η] is the characteristic viscosity; c is the concentration of the solution, mg / L; K and α are constants related to the properties, concentration and test temperature of the solution, which are 0.0085 and 0.76 respectively; M η is the viscosity molecular weight.

[0063] The test method for complete swelling maturity is as follows: 5g of sample is added to a beaker containing 50g of saturated calcium hydroxide solution, placed in a 20°C constant temperature water bath and magnetically stirred. During the stirring process, the suspension in the beaker is heated at a rate of 1°C / 5min until the suspension is completely transformed within 5min and exhibits the translucent characteristics of a colloid, and the hydration temperature rise inhibitor particles in the solution are observed using a polarizing microscope to completely lose the polarization cross. The product of the temperature at this time and the conversion time is the complete swelling maturity.

[0064] The characteristic parameters are shown in Table 1.

[0065] Table 1 Characteristic parameters of samples obtained in Examples and Comparative Examples

[0066]

[0067] As can be seen from Table 1, by adopting the preparation method provided by the present invention, a hydration temperature rise inhibitor with a fineness of 10% to 30% and a viscosity average molecular weight of 25,000 to 30,000 can be obtained. Under this characteristic parameter, its full swelling maturity is 150 to 250°C·min, which can better match the typical temperature range (generally 30 to 50°C) at which large-volume concrete begins to heat up rapidly. When the moisture content, pH, dry heat temperature or time exceeds the set value, it will cause a large fluctuation in the viscosity average molecular weight, and the full swelling maturity will be too low or too high, which will affect its final peak shaving effect.

[0068] The semi-adiabatic temperature rise test of mortar with a basic mix ratio of 700g cement, 900g sand and 190g water was used to test the sample performance of Examples 1 to 10 and Comparative Examples 1 to 4. Among them, the cement is P•O42.5 ordinary Portland cement produced by Sichuan Dujiangyan Lafarge Cement Co., Ltd., the sand is ISO intermediate standard sand, and the water is domestic water. The specific test method is: a polyethylene mortar container (size: φD=10cm, φd=7cm, L=17cm) is placed in the middle of an expanded polystyrene insulation box with a size of 40cm×40cm×40cm. After the mortar is mixed, 1750g of the mixture is quickly weighed and added to the mortar container. A multi-channel temperature tester (including thermistor wire and data acquisition device) is used to insert the thermistor wire into the center of the mortar container, and the terminal is connected to the data acquisition device. Close the insulation box, use a polyurethane foaming agent to seal the gap between the upper and lower boxes, and wrap it with transparent tape to fix it. During the mortar center temperature collection process, the ambient temperature was 20±1℃.

[0069] The test results of mortar performance are shown in Table 2. The temperature test results of the mortar after adding the hydration temperature rise inhibitor of Examples 1 to 10 are as follows: Figure 1 The heating rate of the mortar after adding the hydration temperature rise inhibitor of Examples 1 to 10 is shown in Figure 2 The temperature test results of the mortar after adding the samples prepared in Comparative Examples 1 to 4 are as follows: Figure 3 After adding the samples prepared in Comparative Examples 1 to 4, the heating rate of the mortar is as follows: Figure 4 .

[0070] Table 2 Performance test results of samples obtained from examples and comparative examples

[0071]

[0072] It can be seen from Table 2 that after adding 0.5% to 1.0% of the hydration temperature rise inhibitor of the embodiment, the maximum temperature rise of the mortar was reduced by 8.5 to 21.7°C, the initial setting time (time to start rapid temperature rise) was extended by 0.8 to 6.6 hours, and the maximum temperature rise rate was reduced from 11.0°C / h to 1.5 to 5.9°C / h. After adding 1% of the samples of comparative examples 1 to 3, the maximum temperature rise of the mortar was only reduced by 3.2 to 4.4°C, the initial temperature rise time was extended by 9.3 to 35 hours, and the maximum temperature rise rate remained at a high level of 9.9 to 11.3°C / h, which is difficult to meet the needs of temperature control and crack prevention of large-volume concrete. After adding 1% of the sample of comparative example 4, although the temperature peak of 9.0°C can be reduced, the initial setting time is simultaneously extended by more than 20 hours, which is difficult to meet the requirements of early demolding and strength development of concrete.

[0073] The above is only a preferred embodiment of the present invention. It should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art shall not deviate from the spirit and scope of the present invention, and shall be within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing a hydration temperature rise inhibitor with strong peak clipping and weak retarding, characterized in that: The following steps are involved: S1. Mix starch, accelerator and water in a mass ratio of 100:0.04-0.25:40-70 to prepare starch slurry; S2, drying the starch slurry at 40-60° C. to obtain pre-dried starch with a moisture content of 10%-15% and a liquid phase pH of 13.0-13.5; S3, dry-heat cracking the pre-dried starch at 155-185°C for 2-4 hours, grinding and sieving after natural cooling to obtain a hydration temperature rise inhibitor; The starch is one or more of wheat starch, potato starch, rice starch, tapioca starch, sweet potato starch or corn starch; The accelerator is one or more of lithium hydroxide, sodium hydroxide, potassium hydroxide, sodium carbonate or potassium carbonate.

2. The preparation method according to claim 1, characterized in that: The product in S3 is placed in air for natural cooling, ground and passed through a 50-mesh sieve.

3. A hydration temperature rise inhibitor with strong peak clipping and weak retarding, characterized in that: The hydration temperature rise inhibitor prepared by any one of the preparation methods of claims 1-2 has a viscosity average molecular weight of 25000-30000, a complete swelling maturity of 150-250°C·min, and a 200-mesh sieve residue of 10%-30%.

4. The use of the strong peak clipping and weak retarding hydration temperature rise inhibitor in concrete according to claim 3, characterized in that: The dosage is 0.5%~1.0% of cement mass.